Several Factors Affecting Firm Value Manufacturing in Indonesia - Muslim Muslim, Hamzah Ahmad (Jurnal Akuntansi, 2022)
This study aims to examine the effect of Total Asset Turnover, Debt to Equity Ratio, Current Ratio, and Return On Equity on firm value. This type of research includes causal research using quantitative methods. The population in this study are all manufacturing companies listed on the Indonesia Stock Exchange, as many as 183 companies. This technique is based on specific criteria estimated to be related to this study's previously known population and needs. So the total sample for this research is 48 data from 16 companies during 2018- 2020. Secondary data was collected through the Indonesia Stock Exchange website and analyzed using Multiple Regression Analysis with the Ordinary Least Square model using the Eviews Version 12 software. The results found that Total Asset Turnover (TATO) has a negative and insignificant effect on firm value, Debt to Equity Ratio (DER) has a negative and significant effect on firm value, Current ratio (CR) has a positive and insignificant effect on firm value. In contrast, Return On Equity (ROE) has an insignificant effect on firm value. Positive and significant to the value of the company.